2010
DOI: 10.1021/ja910526z
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Structure and Dynamics in Solid Octafluoronaphthalene from Combined NMR, Diffraction, And Molecular Dynamics Studies

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 36 publications
3
35
0
Order By: Relevance
“…In our previous studies of this material we showed that even 100 ns long molecular dynamics simulations are insufficient to sample the full rotation of the molecules, a process shown to occur by solid-state NMR. 32 Our first goal here is to show that the use of metadynamics can make the sampling of this rotation facile, confirming both the effectiveness of the method and further validating the NMR results in that study. Secondly, we extend the method to sample from the simultaneous rotational behavior of three neighboring OFN molecules, proving that they are correlated and investigating the mechanism behind the effect.…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…In our previous studies of this material we showed that even 100 ns long molecular dynamics simulations are insufficient to sample the full rotation of the molecules, a process shown to occur by solid-state NMR. 32 Our first goal here is to show that the use of metadynamics can make the sampling of this rotation facile, confirming both the effectiveness of the method and further validating the NMR results in that study. Secondly, we extend the method to sample from the simultaneous rotational behavior of three neighboring OFN molecules, proving that they are correlated and investigating the mechanism behind the effect.…”
Section: Introductionsupporting
confidence: 68%
“…We have shown previously using unbiased MD simulations that the movement of OFN molecules is governed principally by their in-plane rotation, 32 the definition of which is described above.…”
Section: Collective Variables For Rotational Motion In Ofnmentioning
confidence: 99%
See 2 more Smart Citations
“…While a variety of NMR parameters are sensitive to dynamics on different timescales, it is often difficult to interpret the results obtained in terms of specific motions. Although molecular dynamics simulations are increasingly used to link NMR observations in molecular solids to molecular-level processes [38], such modelling requires an initial structural model. Interpretation of parameters such as NMR relaxation times is especially difficult in the context of heterogeneous and disordered systems, since the dynamic processes are unlikely to be well defined.…”
Section: Discussionmentioning
confidence: 99%